Efforts to Develop TNI Defense Equipment Technology to Support National Defense Posture - Kuncoro, Very Hadi; Amperiawan, Gita; Ansori, Ansori (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The increasing complexity of global security threats and challenges is the result of technological developments, geopolitical dynamics, changes in the strategic environment, as well as the evolution of potential enemy tactics and strategies. In the midst of this dynamic, the TNI (Indonesian National Army) is faced with increasingly complex tasks to maintain the country's security and sovereignty. The TNI must continue to innovate and develop defense equipment technology that is in line with national defense needs. This research aims to see what the ideal defense posture of the Republic of Indonesia is, the current condition of Indonesia's defense equipment technology in facing these threats, and what gaps must be filled regarding the development of defense equipment technology that is in accordance with the country's ideal defense posture. This research uses qualitative research methods with data collection in the form of literature study. The research results show that the development of defense equipment technology does not only involve the modernization of military equipment, but also collaboration with the technology industry and investment in research and development.